THE EFFECT OF PROBLEM BASED LEARNING MODEL AND MATHEMATIC-LOGICAL INTELLIGENCE TOWARD MATHEMATICS LEARNING ACHIEVEMENT - Wewe, Melkior (Universitas Pendidikan Ganesha, 2017)
This study aims to find out the difference between the model of problem-based learning and the mathematical-logical intelligence towards mathematics learning achievement. This study is a true experimental with specific design of post-test only control group design. The population of this study are all fourth grade students of primary schools in Bajawa sub district. Meanwhile, the sample in this study is determined through random sampling. The result of analysis, it is gained that theÂ learning achievement which usedÂ problem based learningÂ model is higher than the mathematics learning achievement of the students with the conventional learning technique. The calculation from two ways ANAVA results in Fobs 1.793 with sig = 0.184, there is no significant effect of learning interaction model and mathematic-logical intelligence. Since there is no interaction, it also means that there is no significant effect of problem based learning collaborated with mathematic-logical intelligence to the studentsâ learning achievement.Â